Evaluation of the Relationship Between Histopathological Tissue Diagnosis and Endometrial Thickness in Cases with Postmenopausal Bleeding - Mehmet Şükrü Budak; Mehmet Baki Şentürk; Sedat Akgöl; Mehmet Obut; Ali Emre Tahaoğlu; Cihan Toğrul; Ayhan Yıldırım (Medical Network, 2016)
OBJECTIVE: The investigation of the relationship between the endometrial sampling results and the endometrial thicknesses measured by transvaginal ultrasonography (TV-USG) in patients with postmenopausal bleeding. STUDY DESIGN: The results of 235 cases, where endometrial sampling has been made due to postmenopausal bleeding at the Diyarbakır Maternity and Pediatric Hospital between January 2013 and December 2013, have been evaluated retrospectively. RESULTS: In the findings, the mean age is 57.83±8.06 years and the mean parity is 7.73±3.26. In 126 of the findings (53.6%), the endometrial thickness in TV-USG is <5 mm (group 1), and in 109 (46.4%) the endometrial thickness in TV-USG is ≥5 mm (group 2). It has been observed that 53 (22.6%) of the cases have been diagnosed with atrophic endometrium, 43 (18.3%) with endometrial polyp, 34 (14.5%) with deficient material, 28 (11.9%) with secretory endometrium, 19 (8.1%) with proliferative endometrium, 16 (6.8%) with simple endometrial hyperplasia, 12 (5.1%) with irregular proliferative endometrium, 7 (3%) with complex endometrial hyperplasia, 3 (1.3%) with endometrial adenocarcinoma and 3 (1.3%) with endometritis. In Group 1, any abnormal histopathological (endometrial polyp, hyperplasia and adenocarcinoma) findings have not been identified. CONCLUSION: In cases with postmenopausal bleeding, endometrial sampling is important. Endometrial thickness measurement with TV-USG, which is a non-invasive technique, should be used as the first step in the evaluation of the cases. It appears that high parity ratios reduce the endometrium cancer risk.